PENGELOLAAN BADAN USAHA MILIK DESA PENYANGGAR DALAM RANGKA OPTIMALISASI PENDAPATAN ASLI DESA CIPTA KARYA - Solikhin; Yoseph Erbito; Marsela (Mount Hope Economic Global Journal, 2024)
The purpose of this study is how to manage the Village-Owned Enterprise of Penyanggar in order to optimize the original income of Cipta Karya Village". The research method uses a qualitative approach. The data analysis technique uses an interactive model according to Miles and Huberman. Based on the results of the study, it can be concluded that the management of BUMDes Penyanggar is carried out in accordance with the AD/ADRT, requiring the contribution of BUMDes Penyanggar to the original income of Cipta Karya Village and maximizing the utilization of the existence of BUMDes Penyanggar so that it can provide direct benefits to the community of Cipta Karya Village, so that it can support the management of BUMDes Penyanggar in order to optimize the original income of Cipta Karya Village optimally, this can be seen from the existence of BUMDes Penyanggar in Cipta Karya Village has had a good impact on the Village Government and the community of Cipta Karya Village.